Microbially-accelerated consolidation of oil sands tailings. Pathway II: solid phase biogeochemistry - Siddique, Tariq; Kuznetsov, Petr; Kuznetsova, Alsu; Li, Carmen; Young, Rozlyn; Arocena, Joselito M.; Foght, Julia (Frontiers in Microbiology, 2014)
Consolidation of clay particles in aqueous tailings suspensions is a major obstacle to effective management of oil sands tailings ponds in northern Alberta, Canada. We have observed that microorganisms indigenous to the tailings ponds accelerate consolidation of mature fine tailings (MFT) during active metabolism by using two biogeochemical pathways. In Pathway I, microbes alter porewater chemistry to indirectly increase consolidation of MFT. Here, we describe Pathway II comprising significant, direct and complementary biogeochemical reactions with MFT mineral surfaces. An anaerobic microbial community comprising Bacteria (predominantly Clostridiales, Synergistaceae, and Desulfobulbaceae) and Archaea (Methanolinea/Methanoregula and Methanosaeta) transformed FeIII minerals in MFT to amorphous FeII minerals during methanogenic metabolism of an added organic substrate. Synchrotron analyses suggested that ferrihydrite (5Fe2O3. 9H2O) and goethite (α-FeOOH) were the dominant FeIII minerals in MFT. The formation of amorphous iron sulfide (FeS) and possibly green rust entrapped and masked electronegative clay surfaces in amended MFT. Both Pathways I and II reduced the surface charge potential (repulsive forces) of the clay particles in MFT, which aided aggregation of clays and formation of networks of pores, as visualized using cryo-scanning electron microscopy (SEM). These reactions facilitated the egress of porewater from MFT and increased consolidation of tailings solids. These results have large-scale implications for management and reclamation of oil sands tailings ponds, a burgeoning environmental issue for the public and government regulators.